PENGGUNAAN TELENURSING TERHADAP KEPATUHAN MINUM OBAT - Hermawan, Dedi; Astuti Purnamawati, Ditha; Dwi Ariani, Desti (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Hypertension remains a major health problem in Indonesia, with its prevalence increasing each year. It is influenced by factors such as age, gender, and heredity. In 2024, there were 384 hypertension cases reported in the Telok Melano Community Health Center area, North Kayong Regency. Objective: To determine the relationship between medication adherence and telenursing among hypertension patients in the Telok Melano Health Center area. Methods: This quantitative study used a quasi-experimental one-group pretest-posttest design. Data were analyzed using the paired sample T-test to evaluate changes in medication adherence before and after the telenursing intervention. Results: Among 32 respondents, prior to the intervention, 50% showed poor adherence, 28.1% moderate, and 21.9% good. After the telenursing intervention, poor adherence decreased to 9.7%, while moderate adherence increased to 34.4% and good adherence to 56.3%. The paired sample T-test showed a significant relationship between medication adherence and telenursing (p = 0.000 < 0.05). Conclusion: There is a significant relationship between telenursing and medication adherence among hypertension patients in the Telok Melano Community Health Center area. Telenursing can effectively improve patient compliance in managing hypertension and should be considered as part of health service strategies for chronic disease management.